Keraladiaptomus rangareddyi a new genus and new species of Diaptominae (Copepoda, Calanoida, Diaptomidae) from a temporary pond in Mattam, Kerala State, India - Santos-Silva, Edinaldo Nelson; Kakkassery, Francy K; Maas, Sibylle; Dumont, Henri Jean F. (Hydrobiologia, 1994)
Calanoid copepods, belonging to the new genus and species Keraladiaptomus rangareddyi, were collected from temporary ponds in Kerala State, India. The new genus belongs to the family Diaptomidae, subfamily Diaptominae. It is described in detail and its affinity to the related genera, Arctodiaptomus Kiefer, 1932 and Eodiaptomus Kiefer, 1932, discussed. © 1994 Kluwer Academic Publishers.